Zinc Supplementation Reverses Lead-Induced Anxiety-Like Behaviour and Social Deficits in Male Wistar Rats (Nigerian Journal of Physiological Sciences, 2025)
Lead is a highly pervasive environmental toxin that exerts harmful effects on the body systems, especially the nervous system. Zinc is an essential trace element that has been found in eukaryotic cells. Lead has a serious neurotoxic effect via mechanisms such as disruption of the antioxidant defense system and activation of inflammatory mediators (Ramírez Ortega et al., 2021; Virgolini & Aschner, 2021). Despite the extensive knowledge on the neurotoxic effects of lead, effective interventions in mitigating its effects are limited. This study aims to assess the effects of zinc supplementation on lead-induced neurotoxicity in male Wistar rats. Twenty-one male Wistar rats were randomly assigned to three groups with seven rats in each group. Group I served as the control; group II, the lead-treated group, received 0.5% of lead in drinking water for 4 weeks; group III, Pb + Zn group, received 0.5% of lead in drinking water and 25 mg/kg of Zinc supplement by oral gavage for 4 weeks. Behavioral assessments were conducted using the Open Field Test (OFT), Elevated Plus Maze (EPM), and three-chamber sociability test to evaluate anxiety and social behavior. Biochemical and hematological analyses were performed to determine the serum levels of proinflammatory cytokines (IL-1β and TNF-α), total antioxidant capacity (TAC), hematological indices, and electrolytes. The results revealed a significant increase in anxiety and a decrease in social behavior in the Pb-only group. Biochemically, there was a marked elevation in IL-1β and TNF-α, with a significant reduction in TAC in these rats. No marked changes were, however, observed in the serum electrolyte levels across all experimental groups. Contrastingly, zinc supplementation effectively ameliorated these effects. Rats in the Pb + Zn group demonstrated improved neurobehavioral outcomes, decreased levels of pro-inflammatory cytokines, restored antioxidant capacity, and increased Neutrophil to Lymphocytes Ratio (NLR). These findings suggest that zinc confers neuroprotective effects against lead-induced neurotoxicity, likely by modulating oxidative stress and suppressing inflammatory and neuroimmune responses.